Never leave the dogs behind : a memoir - Madia, Brianna (HarperOne, 2024)
"The author of the New York Times bestseller Nowhere for Very Long continues her story with this deeply honest, moving account of a woman walking the line between independence and isolation when she moves to the Southwest desert with nothing and no one but her four dogs"--